Detection and molecular characterization of Giardia isolated from recreational lake water in Malaysia - Lim, Y. A. L.; Ramasame, S. D.; Mahdy, M. A. K.; Sulaiman, W. Y. W.; Smith, H. V. (Springer, 2009)
Nine 50-l surface water samples from a Malaysian recreational lake were examined microscopically using an immunomagnetisable separation-immunofluorescent method. No Cryptosporidium oocysts were detected, but 77.8 of samples contained low numbers of Giardia cysts (range, 0.17-1.1 cysts/l), which were genetically characterised by SSU rRNA gene sequencing. Genotype analyses indicated the presence of Giardia duodenalis assemblage A suggesting potential risk to public health. The present study represents the first contribution to our knowledge of G. duodenalis assemblages in Malaysian recreational water.